2009
DOI: 10.1084/jem.20082118
|View full text |Cite
|
Sign up to set email alerts
|

Negative feedback control of the autoimmune response through antigen-induced differentiation of IL-10–secreting Th1 cells

Abstract: Regulation of the immune response to self- and foreign antigens is vitally important for limiting immune pathology associated with both infections and hypersensitivity conditions. Control of autoimmune conditions can be reinforced by tolerance induction with peptide epitopes, but the mechanism is not currently understood. Repetitive intranasal administration of soluble peptide induces peripheral tolerance in myelin basic protein (MBP)–specific TCR transgenic mice. This is characterized by the presence of anerg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
159
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 139 publications
(168 citation statements)
references
References 65 publications
8
159
1
Order By: Relevance
“…We speculate that FcγRIIB −/− .yaa mice may be protected from cerebral malaria by decreasing the overall inflammatory response to the parasite. The feedback regulatory pathway that reduces acute inflammatory responses in FcγRIIB −/− .yaa mice could involve IL-10, because it has been shown that this pathway provides a feedback control of autoimmune responses (33). Regulation also could involve the M2 macrophages that we detected in greater numbers in the brains of FcγRIIB −/− .yaa mice.…”
Section: Discussionmentioning
confidence: 87%
“…We speculate that FcγRIIB −/− .yaa mice may be protected from cerebral malaria by decreasing the overall inflammatory response to the parasite. The feedback regulatory pathway that reduces acute inflammatory responses in FcγRIIB −/− .yaa mice could involve IL-10, because it has been shown that this pathway provides a feedback control of autoimmune responses (33). Regulation also could involve the M2 macrophages that we detected in greater numbers in the brains of FcγRIIB −/− .yaa mice.…”
Section: Discussionmentioning
confidence: 87%
“…A recent study demonstrated that an in vivo switch in Ag (allergen)-specific Th1 and Th2 cells toward IL-10-producing iTreg by high-dose allergen exposure to mice [29], and that characterization of IL-10/IFN-gproducing human Tr1-like cells showed that they are IL-7R À cells [30]. A recent review states that tDC may induce Th0, Th1, Th2, and Th17 cells to differentiate into IL-10-producing suppressive T cells exhibiting each characteristic through the influence of IL-27 [31] via IL-21 [32], suggesting that in vivo Ag stimulation may induce both effector Th types and iTreg by way of a negative feedback system, as also demonstrated in a recent study [33]. Two recent clinical trials of a cancer vaccine containing depletion of CD25…”
Section: Il-10-producing Cd25mentioning
confidence: 79%
“…A late checkpoint might be the decision whether a pathogenic response will be transient or sustained. Here, the responsiveness to IL-23 whose receptor is not expressed on naïve T cells but on effector T cells that are committed to the Th17 lineage, will determine the acquisition of sustained effector functions which may no longer be exclusively associated with the expression of IL-17.In contrast, it has been shown that committed Th1 cells that keep sensing IL-12 together with sustained TcR stimulation turn on downmodulatory programs and start producing IL-10, which has been shown to be an effector T cell intrinsic mechanism to limit immunopathology [174][175][176][177][178]. This may offer a plausible explanation why the administration of an anti-p40 antibody (ustekinumab) that neutralizes both IL-12 and IL-23, had a zero net effect in patients with RRMS and did not reduce the number of gadolinium enhancing lesions after 23 weeks [179].…”
Section: Resultsmentioning
confidence: 99%